Snap beans in the developing world - Janssen, W. (International Center for Tropical Agriculture, 1988)
The present status of snap beans in the developing world is reviewed. Socioeconomic aspects are mainly discussed. Production, marketing, and consumption features are described and the future potential for the crop is outlined. Constraints to production increases are discussed and the opportunities for research and development of the crop are defined. (CIAT)